Bringing health and social policy together: The case of the earned income tax credit - Arno, Peter S. (2009)
The principal objective of our research is to examine whether the earned income tax credit (EITC), a broad-based income support program that has been shown to increase employment and income among poor working families, also improves their health and access to care. A finding that the EITC has a positive impact on the health of the American public may help guide deliberations about its future at the federal, state, and local levels. The authors contend that a better understanding of the relationship between major socioeconomic policies such as the EITC and the public’s health will inform the fields of health and social policy in the pursuit of improving population health.